Utilization of Moringa Seed Flour as a coagulant, palm fiber, and activated charcoal in an effort to improve domestic wastewater - Maya Roman; Nur Aini Bunyani; Joritha Naisanu (Jurnal Biologi Tropis, 2020)
One local alternative that is available is the use of natural coagulants from the Moringa oleifera L. seed starch plant. Moringa seeds have antimicrobial properties that can reduce substances that should not be present in clean water so that they can purify water for clean water needs. However, the distinctive aroma of moringa is still felt, so it needs to be filtered using coconut shell charcoal and fibers . Research objectives: to determine the characteristics of domestic wastewater (pH, TSS, BOD, oil and fat) and after adding Moringa seeds as a coagulant and coconut shell charcoal and fibers as a filter media . This research was conducted in Nunleu Village-Kupang City and the NTT Provincial Health Laboratory. The method used is experiment and laboratory analysis . Phase I samples were analyzed in the laboratory to determine the characteristics of the initial water. Phase II of water purification experiments with treatment A: coagulant 150 mg / l + 10 cm thick activated charcoal + 10 cm palm thickness. Treatment B: coagulant 150 mg / l + fiber thickness 10 cm + activated charcoal thickness 10 cm. The results showed that the treatments (A and B) could reduce pH, BOD, TSS as well as oil and fat. The pH parameter has decreased tends to be acidic. TSS increased by 58.8% in Treatment (A) , but in treatment (B) there was a decrease of 15%, the TSS content still exceeds the quality standard for domestic waste set by the 2016 Ministerial Regulation, 30 mg/L.The BOD content decreased by 45.2% in treatment A while in treatment B there was a decrease of 58.3% . Furthermore, the oil and fat content was quite low, namely in treatment A there was a decrease of 45.2% while in treatment B there was a decrease of 58.3%.